Developing Google Sites-Based Learning Media to Enhance Junior High School Students’ Literacy Skills: An ADDIE Research and Development Study - Nurwahidah; Nuraeni Kasman; Jumiati; Andi Sadapotto (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aims to develop and examine the effectiveness of Google Sites-based learning media in enhancing junior high school students’ literacy skills, particularly in reading and listening literacy. The study was conducted in response to students’ difficulties in understanding literacy materials through conventional learning media and the increasing need for accessible digital learning platforms in the classroom. This research employed a Research and Development design using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. A mixed-methods approach was used to obtain comprehensive data from students, teachers, and expert validators. The instruments included observation sheets, interviews, questionnaires, expert validation forms, and literacy tests. The developed Google Sites-based media integrated learning materials, videos, quizzes, discussion activities, digital reading resources, and reflection tasks to support interactive and independent learning. The results showed that the media was categorized as valid based on expert validation, practical based on teacher and student responses, and effective based on the improvement of students’ literacy test scores after implementation. These findings indicate that Google Sites-based learning media can be used as an alternative digital learning platform to improve students’ literacy skills and encourage more engaging, flexible, and technology-integrated learning in junior high school education.